2022
DOI: 10.3389/fmars.2022.1023953
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, spectral characteristics, and seasonal variation of dissolved organic matter in the northern Beibu Gulf, South China Sea

Abstract: Dissolved organic matter (DOM) in the land–ocean interface plays a critical role in the global carbon cycle, yet its dynamic is not well understood. Dissolved organic carbon (DOC) in the northern Beibu Gulf was measured seasonally from April 2020 to January 2021. Chromophoric and fluorescent DOM (CDOM and FDOM) were synchronously characterized by absorption and fluorescence spectroscopy. Three fluorescent components were identified from 597 samples using parallel factor analysis, including two humic-like and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Terrestrial C3 plants -25.9 ± 1.2 >20 (Meyers, 1994;Sarma et al, 2014) Terrestrial C4 plants -13.1± 1.2 >20 (Meyers, 1994;Sarma et al, 2014) Soil organic matter -19.2± 2.4 10-14 (Kendall, 1998;Sarma et al, 2014) Sewage -24.8 ± 3.2 7-8 (Andrews et al, 1998;Sarma et al, 2014) Marine organic matter -20.0 ± 2.0 5-9 (Middelburg and Herman, 2007;Ye et al, 2017) Freshwater phytoplankton -30.0 ± 2.0 5-14.6 (Thornton and Mcmanus, 1994;Ye et al, 2017) Cai removal pattern) (Stedmon et al, 2000;Guo et al, 2007;Guo et al, 2014). Previous studies have demonstrated that optical parameters could provide valuable information concerning the source, composition, and transformation of DOM in marine environments (Yang et al, 2015;Zhu et al, 2018;Zhu et al, 2022a). Here, optical parameters clearly revealed the major source of DOM in the surface waters of Qinzhou Bay.…”
Section: Source D 13 C (‰) C/n Referencementioning
confidence: 53%
“…Terrestrial C3 plants -25.9 ± 1.2 >20 (Meyers, 1994;Sarma et al, 2014) Terrestrial C4 plants -13.1± 1.2 >20 (Meyers, 1994;Sarma et al, 2014) Soil organic matter -19.2± 2.4 10-14 (Kendall, 1998;Sarma et al, 2014) Sewage -24.8 ± 3.2 7-8 (Andrews et al, 1998;Sarma et al, 2014) Marine organic matter -20.0 ± 2.0 5-9 (Middelburg and Herman, 2007;Ye et al, 2017) Freshwater phytoplankton -30.0 ± 2.0 5-14.6 (Thornton and Mcmanus, 1994;Ye et al, 2017) Cai removal pattern) (Stedmon et al, 2000;Guo et al, 2007;Guo et al, 2014). Previous studies have demonstrated that optical parameters could provide valuable information concerning the source, composition, and transformation of DOM in marine environments (Yang et al, 2015;Zhu et al, 2018;Zhu et al, 2022a). Here, optical parameters clearly revealed the major source of DOM in the surface waters of Qinzhou Bay.…”
Section: Source D 13 C (‰) C/n Referencementioning
confidence: 53%
“…CDOM has no apparent seasonality and has the lowest concentration in the summer [94]. CDOM in seawater can be divided into two categories according to their sources: in situ degradation of organisms in the ocean and dissolved organic matter in terrestrial soil brought into the ocean through river runoff [29]. Compared with nearshore and estuarine areas, the Nansha Sea area is not influenced by land-based sources and belongs to Class I water bodies with low CDOM content [95].…”
Section: Discussionmentioning
confidence: 99%
“…The flux and degradation of organic carbon play a significant role in shaping microbial communities within the ocean and have far-reaching implications for the carbon cycle in the SCS [2]. Our understanding of carbon cycling in coral reef systems in the SCS is currently limited due to the lack of research on the distribution and seasonal variations of organic carbon in this region, as emphasized by Zhu et al [29]. In the face of increasingly serious ocean acidification, coral reef bleaching is severe, and nearly two-thirds of coral reefs are at risk of extinction [30,31].…”
Section: Introductionmentioning
confidence: 99%